Priorities and Hierarchical Accounts of Translation - Patrick Zabalbeascoa, (Miscelánea: A Journal of English and American Studies, 2006)
This paper is a study of the concept of priority and its use together with the notion of hierarchy in academic writing and theoretical models of translation. Hierarchies and priorities can be implicit or explicit, prescribed, suggested or described. The paper starts, chronologically, with Nida and Levyv’s hierarchical accounts of translation and follows their legacy in scholars as different as Newmark and Gutt. The concept of priorities is hinted at also in didactic models (Nord) as well as in norm-theoretical and accounts of translation (Toury and Chesterman) within Descriptive Translation Studies. All of these authors are analyzed and commented. The paper calls for a more systematic and straightforward account of translational priorities, and proposes a few conceptual tools that stem from this research model, including the concepts of ambition and richness of a translation. Finally, the paper concludes with an adaptation of Lakoff and Johnson’s view of prototypicality and its potential usefulness in research into and the understanding of translation.
Keywords: translation; priorities; hierarchy; prototype; subjectivity